Transanal minimally invasive surgery (TAMIS) for local excision of selected rectal neoplasms: efficacy and outcomes in the first 11 patients - Sevá-Pereira,Gustavo (2014)
Disposable single-port surgery devices have been used for transanal minimally invasive surgery (TAMIS) with benefits, when compared to local resection and transanal endoscopic microsurgery (TEM). Objective: To show outcomes and details of the technique. Method: A series of patients with indication for local resection of rectal tumors were submitted to surgery using the TAMIS platform. Results: Eleven patients have been submitted to TAMIS. Distance from anal verge was from 1.5 to 8 cm and maximum tumor diameter was 6 cm. Initial diagnosis of adenoma was the most frequent indication for resection. One partial dehiscence was the only complication seen. Minimal setup time, low cost and the possibility of using regular laparoscopic instruments make TAMIS a good option for transanal resection. The results of this technique are encouraging, concerning the feasibility, maneuverability, upfront cost, setup time, resectability and complication rate. Because of its simplicity and similarity with conventional laparoscopic surgery, it can be learned easily. Although at the present time the appropriate use of local excision is still under debate, TAMIS is a technique that still expects a lot of growing and much remains to be learned.